Intelligent substation virtual circuit verification method combining knowledge graph and deep learning - Cao, Haiou; Zhang, Yue; Ge, Yaming; Shen, Jiaoxiao; Tang, Changfeng; Ren, Xuchao; Chen, Hengxiang (Frontiers in Energy Research, 2024)
The correctness of the intelligent electronic devices(IEDs) virtual circuit connections in intelligent substations directly affects the stability of the system operation. Existing verification methods suffer from low efficiency in manual verification and lack uniformity in design specifications. Therefore, this paper proposes a virtual circuit automatic verification method that combines knowledge graphs with deep learning. Firstly, this method utilizes expert knowledge and relevant standard specifications to construct a knowledge graph of virtual circuits, integrating knowledge from historical intelligent substation configuration files into the knowledge graph. Then, leveraging multihead attention mechanisms and Siamese neural networks, it achieves matching between the textual descriptions of virtual terminals and standard virtual terminal descriptions. Additionally, a verification process for the virtual terminal port address string is incorporated. Finally, experimental validation confirms the effectiveness of the proposed method and strategy, further enhancing the accuracy of virtual circuit verification.